Dimensões Subjetivas da Ação Docente com o Projeto de Vida - DANIEL VENTURA DAMACENO (2023)
This research aims to investigate the subjective configurations related to the teaching of the Life Project/Purpose curricular component, analyzing the historical-cultural context of its implementation, with emphasis on Rede Estadual de Ensino de Mato Grosso do Sul, as well as, the subjective configurations of the Life Project/Purpose teacher by the fields of intelligibility related to the context of action and pedagogical relationship in the component during the last years and in the context of COVID-19. The research is qualitative, used Qualitative Epistemology and Constructive-Interpretative Methodology, with interviews, questionnaires, and written production as instruments, and produced a theoretical model in line of the Theory of Subjectivity, with contextual analysis by Historical-Cultural Theory. It has done with the participation of five Life Project/Purpose teachers from state schools in Campo Grande, Mato Grosso do Sul. Of these, two composed the theoretical production of this study. It consists of an introductory chapter and four theoretical chapters that present an analysis of the historical, legal, and conceptual devices that led to the emergence of the Life Project, the relationship between the Life Project and Education, the theoretical-epistemological-methodological foundations for the study and research of the subjective dimension, the theoretical production carried out with the two teachers, and a chapter with discussions, limits, and perspectives of the research. The research was approved by the Comitê de Ética em Pesquisa em Seres Humanos da Universidade Federal de Mato Grosso do Sul and had as results: understanding of the fields of intelligibility and the subjective configurations of teaching action in Life Project/Purpose, the neoliberal influence in the emergence of the Life Project/Purpose, the conceptual and pedagogical fragility of the component, the personalization of the conduct of the Life Project/Purpose by teachers, the identification of the development of socio-emotional competencies, the subjective changes in teachers after teaching Life Project/Purpose, the discrepancies of experiences lived in the pandemic, and the need for initial training for Life Project/Purpose teachers considering the subjective dimension in formative processes and recognizing the multiple experiences of teachers, and the understanding that pedagogical actions in Life Project/Purpose can promote the expression of human experience in schooling being a space for authentic dialogues.